2014
DOI: 10.1186/s12983-014-0087-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature tolerance of different larval stages of the spider crab Hyas araneus exposed to elevated seawater PCO2

Abstract: IntroductionExposure to elevated seawater PCO2 limits the thermal tolerance of crustaceans but the underlying mechanisms have not been comprehensively explored. Larval stages of crustaceans are even more sensitive to environmental hypercapnia and possess narrower thermal windows than adults.ResultsIn a mechanistic approach, we analysed the impact of high seawater CO2 on parameters at different levels of biological organization, from the molecular to the whole animal level. At the whole animal level we measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…Our findings on oxygen and acid-base status of haemolymph provide evidence that the T P is also shifted downwards by CO 2 as reported for other marine ectotherms (e.g. Metzger et al 2007;Walther et al 2009;Dissanayake and Ishimatsu 2011;Schalkhausser et al 2012;Schiffer et al 2014; for review see Pörtner 2012). Haemolymph PO 2 was initially slightly increased under hypercapnia but decreased progressively above 19 °C a pattern that only occurred above 22 °C under normocapnia.…”
Section: Co 2 Effects On Thermal Limitssupporting
confidence: 86%
“…Our findings on oxygen and acid-base status of haemolymph provide evidence that the T P is also shifted downwards by CO 2 as reported for other marine ectotherms (e.g. Metzger et al 2007;Walther et al 2009;Dissanayake and Ishimatsu 2011;Schalkhausser et al 2012;Schiffer et al 2014; for review see Pörtner 2012). Haemolymph PO 2 was initially slightly increased under hypercapnia but decreased progressively above 19 °C a pattern that only occurred above 22 °C under normocapnia.…”
Section: Co 2 Effects On Thermal Limitssupporting
confidence: 86%
“…Laboratory and field studies on the development of brachyuran larvae have fostered our understanding of diverse ecophysiological aspects such as phenotypic plasticity in developmental traits, heterochrony in developmental patterns, carry-over effects on life-history traits, and adaptive mechanisms that enhance tolerance to fluctuations in environmental abiotic and biotic factors. Furthermore, a diverse range of biological topics has been analysed using brachyuran larvae as models including aspects of the physiology of aquatic-terrestrial and marine-limnic transitions, dispersal potential of invasive species, adaptive significance of abbreviated development, and effects of acclimation (reviews [ 4 , 7 ]) but also the effects of environmental change-induced abiotic stress on ontogenetic stages of marine organisms [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…2013; Schiffer et al. 2014). In at least one species of crab, the late larval stages show less tolerance to thermal stress than do early larval stages (Storch et al.…”
Section: Introductionmentioning
confidence: 99%
“…The few published studies demonstrate that different life stages often have different thermal tolerances, but do not provide support for a consistent pattern. Studies of crustaceans have found that larval stages have lower thermal tolerance than adults (e.g., Miller et al 2013;Schiffer et al 2014). In at least one species of crab, the late larval stages show less tolerance to thermal stress than do early larval stages (Storch et al 2011).…”
Section: Introductionmentioning
confidence: 99%